Evaluating Entrepreneurial Intention Among Pesantren Students: Fostering Empowerment Through Education - Aji Primanto; Linda Puspitasari (SYAMIL: Journal of Islamic Education, 2023)
Traffic education has the potential to reduce accident rates by changing the behavior and attitudes of road users. Through effective outreach and training, road safety messages can be instilled in public awareness, thereby reducing violations of traffic rules and avoiding risky behavior that causes accidents. Additionally, traffic education also helps improve driving skills and situational awareness, which are important factors in reducing accidents. Which can be taught to children at primary and secondary education levels. The research results show that Traffic Education for Elementary School and Middle School Children is one of the important programs carried out to provide children with an understanding of safe and correct traffic procedures. This program aims to provide knowledge and skills to children in dealing with various traffic situations around them. Traffic education for elementary school and MI children is carried out in stages and is adjusted to the child's age and development level. Civics and Religion are subjects that are able to contribute to solutions to the various crises that hit Indonesia, especially multidimensional crises related to Values, Norms, Morals and Traffic Ethics through Education.